2016
DOI: 10.1007/s00259-016-3467-5
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of cardiac cadmium-zinc-telluride gamma camera imaging in coronary artery disease: a review from the cardiovascular committee of the European Association of Nuclear Medicine (EANM)

Abstract: The trade-off between resolution and count sensitivity dominates the performance of standard gamma cameras and dictates the need for relatively high doses of radioactivity of the used radiopharmaceuticals in order to limit image acquisition duration. The introduction of cadmium-zinc-telluride (CZT)-based cameras may overcome some of the limitations against conventional gamma cameras. CZT cameras used for the evaluation of myocardial perfusion have been shown to have a higher count sensitivity compared to conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 61 publications
0
40
0
1
Order By: Relevance
“…8,9 Given their groundbreaking technical features and the differences between the two available but competing suites (D-SPECT, Spectrum Dynamics, Palo Alto, CA, USA; Discovery NM 530c or Discovery NM/CT 570c with Alcyone technology, GE Healthcare, Haifa, Israel), there are, however, ongoing developments and refinements in the application of this imaging technology to current cardiovascular practice. [10][11][12] Accordingly, the scholarly literature on CZT MPI is continuing to expand momentously, as demonstrated by the work by Jameria and colleagues published in this issue of the Journal. 13 Specifically, Jameria et al report hereby a singlecenter retrospective observational study comparing acquisition of MPI with CZT vs Anger cameras, and focusing on several protocol subtleties such as stressonly vs stress-rest acquisition, and upright vs supine positioning, while using a D-SPECT suite and relying on coronary angiography as gold standard.…”
Section: See Related Article Pp 540-549mentioning
confidence: 99%
“…8,9 Given their groundbreaking technical features and the differences between the two available but competing suites (D-SPECT, Spectrum Dynamics, Palo Alto, CA, USA; Discovery NM 530c or Discovery NM/CT 570c with Alcyone technology, GE Healthcare, Haifa, Israel), there are, however, ongoing developments and refinements in the application of this imaging technology to current cardiovascular practice. [10][11][12] Accordingly, the scholarly literature on CZT MPI is continuing to expand momentously, as demonstrated by the work by Jameria and colleagues published in this issue of the Journal. 13 Specifically, Jameria et al report hereby a singlecenter retrospective observational study comparing acquisition of MPI with CZT vs Anger cameras, and focusing on several protocol subtleties such as stressonly vs stress-rest acquisition, and upright vs supine positioning, while using a D-SPECT suite and relying on coronary angiography as gold standard.…”
Section: See Related Article Pp 540-549mentioning
confidence: 99%
“…Conventional SPECT MPI has a sensitivity ranging between 0.82 and 0.91, and specificity ranging between 0.70 and 0.90. 2 During the first decade of the twenty first century, CZT SPECT systems emerged promising ultrafast acquisition, dose reduction, and similar diagnostic accuracy. The direct conversion of gamma radiation into signal by the semiconductor ensured improved image fidelity.…”
Section: Czt Versus Conventional Spectmentioning
confidence: 99%
“…2 Many of these studies have assessed the diagnostic performance of MPI with CZT cameras (Table 1). 1,[3][4][5][6][7][8] Further, in a meta-analysis by Nudi et al, the sensitivity of CZT SPECT was found to be range between 0.78 and 0.89 and the specificity ranged from 0.62 to 0.76.…”
Section: Czt Versus Conventional Spectmentioning
confidence: 99%
“…[4][5][6] It improved image quality and patient comfort. Its diagnostic performances compare favorably with those of conventional SPECT.…”
mentioning
confidence: 99%